The Relationship between the Framing of Speeding Messages and Changes in Attitude of Generation Z Respondents - Uricska, Erna (Magyar Rendészet, 2023)
Police communication with the public is a vital process, and it should be considered a key area of research in the digital era. Until the 2000s, police messages reached the community through traditional media channels. Nowadays, there is an opportunity for e-community policing: to identify problems in the online sphere, propose solutions and improve police-community relations through the appropriate use of social networking sites. This study is a pioneering one as no research has yet been carried out that analysed the visual effects of Hungarian police communication on social media. The observed sample was collected by systematic sampling and, using the perspective of emotions as frames, a questionnaire survey was conducted among Generation Z members to investigate the elicited emotions and their persuasive effects. The aim of this empirical research is to demonstrate that visuals created by the police may be of particular importance in crime prevention.